ANALISIS PERBEDAAN ANTARA KURIKULUM KTSP DAN KURIKULUM 2013 - Lukmanul Hakim (Jurnal Ilmiah Didaktika, 2017)
A curiculum as a teaching program of one of the instutions may have changed in accodance with the need of the society. In Indonesia, the government under the administration of the Ministry of National Education has made the changes of curriculum for several times, such as, KTSP 2006 (unit lesson-based curriculum) and Kurikulum berbasis karakter2013 (character-based curriculum).These changes are aimed at developing the quality of education in this country. This writing discusses the differences between KTSP 2006 and Kurikulum berbasis karakter 2013. Through the discussion, it is found that there are some differences between both of these curriculum in many aspects in lessons focused, methods applied, students’ achievement scale, and teaching learning goals.